Gasless laparoendoscopic single-site surgery for management of unruptured tubal pregnancy in a woman with moderate COVID-19 pneumonia after administration of remdesivir and casirivimab-imdevimab: A case report - Shotaro Hayashi; Akihiro Takeda (Elsevier, 2022)
Background: Diagnostic and therapeutic challenges may arise in the management of gynecologic emergencies, such as ectopic pregnancy, for women with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. Case: A 33-year-old woman (gravida 3, para 2) with a history of SARS-CoV-2 infection 8 months prior experienced sudden onset of fever and cough. Four days later, she consulted her gynecologist because of a positive pregnancy test and was further referred because of suspected ectopic pregnancy at 11 weeks of gestation, as calculated from her last irregular menstrual period. At triage, the patient complained of dyspnea, chest pain, and cough. Real-time reverse transcription-polymerase chain reaction assay detected SARS-CoV-2, which was subsequently identified to be an L452R variant. Chest computerized tomography (CT) showed moderate COVID-19 pneumonia. Transvaginal ultrasonography and pelvic CT showed a right tubal mass without an intrauterine gestational sac, suggesting right tubal pregnancy. Systemic methotrexate (MTX) therapy was chosen for management of the tubal pregnancy because of the patient's unruptured hemodynamically stable status, along with immediate administration of remdesivir and casirivimab-imdevimab to prevent worsening of the pneumonia. After failed MTX therapy, gasless laparoendoscopic single-site right salpingectomy was performed due to concern for tubal rupture. Four days after surgery, the patient was discharged from the hospital without subsequent complications. Conclusions: Laparoscopic surgery, preceded by anti-viral therapy for COVID-19, is a feasible option for the management of hemodynamically stable tubal pregnancy in a woman with moderate COVID-19 pneumonia.